Desistance and children: critical reflections from theory, research and practice - Wigzell, Alexandra; Paterson-Young, Claire; Bateman, Tim (Policy Press, 2024)
Available open access digitally under CC BY-NC-ND licence. ‘Desistance’ - understanding how people move away from offending – has become a significant policy focus in recent years, with desistance thinking transplanted from the adult to the youth justice system in England and Wales. This book is the first to critique this approach to justice-involved children, many of whom are yet to fully develop an identity (criminal or otherwise) from which to ‘desist’. Featuring voices from academia, policy and practice, this book explores practical approaches to desistance with children in the ‘Child First’ context. It gives new insights into how children can be supported to move away from offending and proposes reforms to make a meaningful difference to children’s lives